Improved boiler-turbine coordinated control of 1000 MW power units by introducing condensate throttling. (February 2017) - Wang, Wei; Li, Lu; Long, Dongteng; Liu, Jizhen; Zeng, Deliang; Cui, Can
Highlights: A 4-inputs 3-outputs model collaborating coordinated control and condensate throttling is proposed. A dual controller is designed to cooperate fuel flow control with condensate throttling control. A stable inversion system is solved to reduce the boiler delay. A decoupling controller is designed to ensure the control performance. Our strategy's load-change rate is four times faster than traditional method. Abstract: Improving the operating flexibility of coal-fired units has become more and more important since an increasing number of fluctuant renewable energy connected to the power grid would make the power system easily unstable. However, it is difficult for the 1000 MW power units to improve their load change capability because the large delay of their once-through boilers. In this paper, the condensate throttling and coordinated control are combined to accelerate the load response, and a 4-inputs 3-outputs control model is firstly set up. Then a dual controller is designed to realize the combination control of fuel flow and condensate water flow on turbine load; also, the dual controller can recover the condensate water flow and deaerator level to their former values. Furthermore, the feedforward control based on stable inversion is developed to advance the response of fuel regulation, and the main steam pressure control and separator outlet enthalpy control are decoupled for convenient control. Finally, simulation tests and analyses on a 1000 MW unit are carried out to prove the effectiveness of our strategy.